Reviewing vegetation indices for mobile application: potentials and challenges - Sulaiman, Puteri Suhaiza; Khalid, Fatimah; Azman, Azreen; Kahar, Zainal Abdul; Hanafi, Marsyita (Semarak Ilmu Publishing, 2024)
Vegetation are quantitative metrics that are used to assess the density of vegetation as well as its health and vitality. Vegetation indices are important in precision agriculture and monitoring environmental conditions. For years, vegetation indices have been derived from remote sensing or aerial imaging data, with focus on large plantation estate and green coverage. Recently, there is a growing interest in using mobile phone for measuring vegetation indices at a more affordable cost. The spectral range for vegetation indices extends from 400 nm to 900 nm, which places it in the VIS and NIR spectral categories, respectively. The CMOS sensor that is typically found in mobile phone cameras has the capacity to capture NIR images. This paper aims to give a background in understanding vegetation indices available and weighing the suitability of using these indices for mobile applications. The potential of using these indices has been establish when the studies indicate several works have successfully used mobile phone camera to capture vegetation indices formulation, but still additional features is needed to ensure the standardisation and consistency of image calibration. © 2024, Semarak Ilmu Publishing. All rights reserved.